Implementasi Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa SD Inpres Saramom, Kabupaten Biak Numfor - Iriawan, Hermanu; Iswahyudi Iswahyudi; Edyanto Edyanto (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
PHBS in Schools is a behavior to empower students, teachers and the community in the school environment to be willing to implement and practice the PHBS pattern in order to create a clean and healthy school environment. PHBS socialization is one of the lecturer's community service programs. This PHBS socialization can be carried out through cooperation between the Institute of Social and Political Sciences (IISIP Yapis Biak) with Pertamina FT, Biak City PUSKESMAS, and the SD INPRES Saramom Teachers Council. This activity was carried out on Wednesday, January 15, 2025 which took place in the SD INPRES Saramom room. The students were very enthusiastic about receiving the socialization given. It is hoped that the PHBS socialization material will be implemented in everyday life.